PENGARUH RESPONSIVENESS, EASE OF USE, RELIABILITY, CONVENIENCE, FULFILLMENT, DAN SECURITY AND PRIVACY TERHADAP CUSTOMER SATISFACTION MANDIRI MOBILE - SURAHMAN PUJIANTO (Jurnal Bisnis dan Akuntansi, 2018)
The purpose of this research is to test and analyze empirically the influence of Responsiveness, Ease of Use, Reliability, Convenience, Fulfillment, Security and Privacy toward Customer Satisfaction. The research design used in descriptive research and causality research, in which variables are measured with 5 points Likert scale. This research used primary data which collected by questionnaire. The sampling in the study was purposive sampling and used 130 respondents. The research data is processed with SPSS statistics program. The result of this research has shown that Responsiveness, Ease of Use, Reliability, Convenience, Security and Privacy have influence to the Customer Satisfaction. While Fulfillment do not has influence to customer Satisfaction.